2023
DOI: 10.1038/s41591-023-02213-x
|View full text |Cite
|
Sign up to set email alerts
|

In-depth virological and immunological characterization of HIV-1 cure after CCR5Δ32/Δ32 allogeneic hematopoietic stem cell transplantation

Abstract: Despite scientific evidence originating from two patients published to date that CCR5Δ32/Δ32 hematopoietic stem cell transplantation (HSCT) can cure human immunodeficiency virus type 1 (HIV-1), the knowledge of immunological and virological correlates of cure is limited. Here we characterize a case of long-term HIV-1 remission of a 53-year-old male who was carefully monitored for more than 9 years after allogeneic CCR5Δ32/Δ32 HSCT performed for acute myeloid leukemia. Despite sporadic traces of HIV-1 DNA detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 29 publications
0
54
0
2
Order By: Relevance
“…36 The ongoing research on stem cell transplantation and alternative ART approaches could improve the quality of life with HIV even more, reducing problems with compliance and the risk of opportunistic infections or resistance to ART (i.e., injectable HIV treatment). [37][38][39] The strengths of our work embrace the sample size of 22 articles with individual data on 29 HIV-positive patients receiving ECMO support, comprising the global knowledge. Moreover, we performed a systematized search of two major databases, including gray literature and the lists of references of included studies, ensuring the comprehensiveness of our search.…”
Section: Discussionmentioning
confidence: 99%
“…36 The ongoing research on stem cell transplantation and alternative ART approaches could improve the quality of life with HIV even more, reducing problems with compliance and the risk of opportunistic infections or resistance to ART (i.e., injectable HIV treatment). [37][38][39] The strengths of our work embrace the sample size of 22 articles with individual data on 29 HIV-positive patients receiving ECMO support, comprising the global knowledge. Moreover, we performed a systematized search of two major databases, including gray literature and the lists of references of included studies, ensuring the comprehensiveness of our search.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that individuals with a non-functional allelic variant of this gene ( CCR5Δ32 ) are protected from CCR5-tropic HIV infection [ 52 ]. Moreover, the three published cases of cured individuals known to date, i.e., the Berlin, London, and Dusseldorf patients [ 16 , 18 , 53 , 54 ], underwent allo-HSCT with cells from donors who were homozygous for the CCR5 deletion ( CCR5Δ32/Δ32 ). In a clinical trial, Tebas and colleagues [ 55 ] demonstrated the safety and feasibility of a therapy that attempted to mimic the genetic inherited resistance to HIV in individuals carrying the CCR5Δ32/Δ32 deletion.…”
Section: Difficulties and New Strategies To Achieve Hiv Cure With Car...mentioning
confidence: 99%
“…In January 2011, the patient was diagnosed with AML-M2 (French-American-British classification), carrying inversion of chromosome 16 at p13q22, resulting in the CBFB-MYH11 fusion protein. After chemotherapy, which included idarubicin, cytarabine and Age at the time of stem cell transplantation ~40 [9] 36-37 [62] Middle aged [18] 63 [20] 43 [23] 2.…”
Section: The Düsseldorf Patientmentioning
confidence: 99%